Privato o pubblico in antropologia: that is the question - Villa, Marta (Antropologia Pubblica, 2024)
The academic society has been questioned at length and has issued Codes Ethics to determine the behavior to be held in respect of indigenous peoples and traditional societies examined: data may have different levels of diffusion and they must be shared by communities. Anthropologists need to ask the permission to get inside of the societies investigated. Some cases highlight how these relations of the report are hardly maintained by both sides. The delicate relationship between scholars and privileged informants may be damaged if the disclosure of information occurs without sharing and respect. In conclusion we analyze the case of the publication post mortem of Malinowski's diaries: is it a case of privacy's violation? What is the usefulness?